Core‐Shell Functionalized Zirconium‐Pemetrexed Coordination Nanoparticles as Carriers with a High Drug Content. Issue 11 (24th September 2019) - Steinborn, Benjamin; Hirschle, Patrick; Höhn, Miriam; Bauer, Tobias; Barz, Matthias; Wuttke, Stefan; Wagner, Ernst; Lächelt, Ulrich
Abstract: Selected drug molecules with Lewis base functions can be assembled into coordinative nanoparticles (NPs) by linking them with suitable metal ions. Such nanomaterials exhibit a high material economy due to high drug contents and minor amounts of inactive additives. The antifolate pemetrexed (PMX) which is used for the treatment of lung cancers contains two carboxy functions that are able to undergo coordinative binding of metal ions. This study presents the development of a multilayer PMX NP system where each layer serves a distinct purpose. The metal‐drug NP core is assembled in a bottom‐up approach by coordinative interactions between zirconium (IV) ions and PMX molecules. Since the NP core is generated from drug molecules as essential units, it features a very high drug content of almost 80%. The NP core is stabilized against serum with a shell of a polymerized oligoamine‐modified trimethoxysilane derivative (TMSP). As external layer, a polyglutamate‐ block ‐polysarcosine‐N3 (pGlu‐ b ‐pSar) coating mediates efficient colloidal stabilization and enables introduction of targeting functionalities by click chemistry. Attaching folate or transferrin ligands to the polymer layer enhances NP uptake into target receptor positive KB and L1210 cells. This study illustrates the development and characterization of metal‐drug coordination NPs with high drug content and variable external functionalizations. Abstract : This study presents a multilayer chemotherapeutic nanoparticle based on a coordinative zirconium‐pemetrexed core with a drug content of almost 80%. Coating with an oligoamine‐modified silica‐reagent increases serum stability. Subsequent functionalization with a targeted polyglutamate‐polysarcosine block copolymer as the outermost layer simultaneously mediates efficient shielding, increases colloidal stability, and enhances nanoparticle uptake into cancer cells by addressing target receptors.